El Ordenador al Servicio del Aprendizaje de Lenguas: Gramática y Diccionario Automáticos del Español - Lebredo, María Concepción Álvarez (The ESPecialist, 2012)
In second language learning, it is essential to know the syntactical-semantic valency of verbs. Non-native speakers may take advantage of tools, such as grammars and dictionaries. However, in the case of Spanish, those tools, although they give a great deal of data, are not suitable for L2 acquisition. The valency information they contain is not sufficiently explicit to allow the encoding of admissable messages in Spanish. Here we try to show an automatic recognition system which first analyses the verb constructions proposed by the user and secondly shows the verb meaning which is implied in the example. Grammar, dictionary and machine joint efforts in the process of learning.